2014
DOI: 10.5430/ijba.v5n6p48
|View full text |Cite
|
Sign up to set email alerts
|

Competition as a Response Strategy to Globalization by Manufacturing Firms in Kenya

Abstract: Globalization affects local and international firms in many ways. Studies have shown that factors in the internal as well as external environments of firms influence the rate to which globalization will affect them. On the local scene however, no known studies have been done on the response of Kenyan manufacturing firms to counter globalization. In addition, since the concept of globalization is multidimensional and its influence is varied in nature, this study aimed at investigating how manufacturing firms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Hence, independently TQM has no mediating effect on the relationship between MPS and BTS as zero did fall within the lower and upper limit of the confidence interval. Although there was no priori basis for the hypothesis, the study expected a positive mediating effect of TQM on the relationship between MPS and BTS according to non-related studies (Prajogo & Sohal, 2006;Simani et al, 2017). These relationships had not been examined before in the context of the BTS.…”
Section: Discussionmentioning
confidence: 95%
“…Hence, independently TQM has no mediating effect on the relationship between MPS and BTS as zero did fall within the lower and upper limit of the confidence interval. Although there was no priori basis for the hypothesis, the study expected a positive mediating effect of TQM on the relationship between MPS and BTS according to non-related studies (Prajogo & Sohal, 2006;Simani et al, 2017). These relationships had not been examined before in the context of the BTS.…”
Section: Discussionmentioning
confidence: 95%
“…People are among the most important resources available to firms in an inquest into the firm's leadership, and competitive advantage. One could argue that firms achieve competitiveness through product branding and adoption of new ways of approaching markets and also through re-organizing themselves strategically (Parker & Van Alstyne, 2005;Raymond & Uwizeye Mungu, 2007;Ismail, Rose, Uli & Abdullah, 2012;Kinyanjui, Oloko, Gachunga & Gathondu, 2014), forgetting that people (human) are the most important firm's asset and managing people(human) can be linked to attaining competitive advantage. Previous scholars have indicated that the human element is becoming increasingly important in generating economic value (Conner & Prahalad, 1996;Snell, Shadur & Wright, 2005).…”
Section: Background Introductionmentioning
confidence: 99%
“…resent day globalization has led to heightened competition among business firms (Kinyanjui et al, 2016), and created a business environment that is turbulent and highly competitive (Schwab, 2019). Consequently, firms are forced to find unique ways of creating and sustaining competitiveness for their survival (Laban and Deya, 2019).…”
Section: Introductionmentioning
confidence: 99%